Access Control and Security System Via Bluetooth Application on Android Smartphone - Amiliansyah, Husna; Galina, Mia; Welman, Joni (Jurnal ELTIKOM : Jurnal Teknik Elektro, Teknologi Informasi dan Komputer, 2022)
Smartphone technology can be applied not only to establish communication needs but also to support other purposes. One of them is related to personal safety and security functions. It is undeniable that criminal acts can occur anytime and anywhere. Even in a private or residential area, theft could happen. Smartphone and sensor technology can be used as a solution to encounter this problem. In this case, it can be utilized to improve the security control system of the gate or garage door at home. This research presents a prototype of a gate and garage door control and security system that operates through an application on an android smartphone. The application of HC-05 Bluetooth is used to send signals from the smartphone to the Arduino Uno microcontroller, while the micro servo acts as a locking mechanism on the gate itself. The buzzer function is presented to notify homeowners when the gate or garage door is open for more than 15 seconds. This prototype can control gates and garage doors with an average connection time of only about 5 seconds. Thus, this prototype is feasible to use as an alternative to control and improve housing security systems.